Between Global Market of Contemporary Art and Death: the Work of Teresa Margolles - Mora Solano, Sindy (2021)
This paper analyzed the work of the Mexican artist Teresa Margolles. It exposes the thesis that her work has been positioned in the global art market, promoted by the “permissive paradox” of the institutionality of contemporary art. Through this mechanism, Margolles has exported, from the periphery to the center, an art that emphasizes images of violence and death, transforming violence and death into exotic objects of exhibition in European and American museums. In the paper are analyzed ¿De qué otra cosa podríamos hablar? (2009), La Promesa (2012) and El Testigo (2014).